Impact of Early versus Delayed Excision and Grafting on Wound Healing and Treatment in Burn Injuries: A Retrospective Study - Saleem, Shahan; Kant, Bashir ur Rehman; Zafar, Alina; Ahmed, Saqlain; Akbar, Aiza Ali; Syeda , Wajiha Batool (Indus Journal of Bioscience Research, 2024)
Background: Injuries from burns have an important effect on public health, especially in low- and middle-income nations, resulting in substantial mortality, morbidity and economic loss. The timing of excision and grafting is a key aspect in patient outcomes especially when it involves hypertrophic formation of scars. Methods: This retrospective study, performed at a top burn therapy centre in Islamabad, Pakistan, investigated the medical histories of patients who had been treated for deep cutaneious or full thickness burns. Patients were separated into two groups based on when they received their surgical intervention: early excision and grafting (EEG) within a week after damage and delayed excision and grafting (DEG) after one week. The primary outcome studied was the frequency and seriousness of hypertrophic scar development, which was determined using a conventional scar evaluation scale. Results: The study examined 100 patients and found that those enrolled in the EEG group had considerably better outcomes in terms of hypertrophic scar formation, hospital stay duration, rates of infection, and overall treatment expenses compared to the DEG group. The study emphasized the significance of early surgical treatments in improving burn treatment outcomes and the need for dedicated burn care facilities. Conclusion: Early excision and grafting within one week of suffering a burn injury greatly minimize the risk and severity of hypertrophic scars, decrease stays in the hospital, and reduce the incidence of infection and treatment costs.